Assembly and testing of a driving simulator - Yeo, Nicholas Xiang Ling. (2011)
This report documents the process and setting up of a driving vehicle simulator. In addition, it contains the results of a study on jackknifing of articulated trucks as part of a continuation study on Port of Singapore Authority (PSA) trucks. The project was initially commissioned by PSA in August 2009.